Biodegradable Plant Pots from Bacterial Cellulose Production by Komagataeibacter nataicola TISTR 975 from Agricultural Waste Materials - Binma-ae, Hatsalinda; Sahoh, Suraiya; Doloh , Mukminah; Hajiwangoh, Zubaidah (YRU Journal of Science and Technology, 2023)
Currently, there is a large amount of agricultural wastes which are the environmental problems. The objective of this research was to develop the production of bacterial cellulose sheets by Komagataeibacter nataicola TISTR 975 from agricultural wastes which are low-cost substrates including melon peel juice, corncob juice, sugarcane bagasse juice, water hyacinth juice and coconut water for biodegradable plant pots production. When comparing the thickness of bacterial cellulose sheets from K. nataicola TISTR 975, the highest thickness of bacterial cellulose sheets was found in coconut water followed by melon peel juice and corncob juice respectively. Those bacterial cellulose sheets had tensile strength of 37.8-79.1 MPa. Fourier Transform Infrared Spectroscopy (FT-IR) showed the chemical structure of cellulose. Scanning electron microscope (SEM) morphology showed a fibril network, and began to decompose at 215-300 ºC. Bacterial cellulose sheets produced from 3 types of low-cost substrates were studied on characterization and molding biodegradable plant pots. The result showed that the rate of water absorption of the pots was 257-558 % and they were completely biodegraded within 30 days. Therefore, the bacterial cellulose sheets produced using K. nataicola TISTR 975 was able to used for biodegradable plant pot production.